The WMPI Architecture for Dynamic Environments and Simultaneous Multiple Devices - Pedroso, Hernâni (2000)
WMPI was originally based on the MPICH implementation. MPICH’s architecture, though well fitted for portability and performance, is not flexible enough to allow the implementation of the new functionality introduced in the MPI-2 standard. Due to this difficulty, we decided to develop a new architecture from scratch. This architecture introduces new concepts that allow for the dynamic creation and termination of processes as well as the usage of simultaneous multiple devices. The new architecture was designed to be completely thread safe and to allow a rapid development of libraries for any communication medium. This paper describes the reasons for developing thr new architecture and presents the implemented solutions to achieve the proposed goals.